A systematic review of self-monitoring interventions in promoting physical activity among adolescents in South Asian Countries - Tengku Kamalden, Tengku Fadilah; Wickramarachchi, Shashini Anushka; Soh, Kim Geok; Gasibat, Qais (Horizon Research Publishing, 2020)
The emphasis is on puberty, as this is a crucial period of the growth of becoming overweight and obese due to inadequate eating habits and physical inactivity. Lifestyle risk factors are not well known to the South Asian people. The purpose of this review is to determine whether self-monitoring physical activity (PA) programmes can be an effective tool to improve PA levels in school-age children and adolescents, hence be adopted to serve as a platform for additional research. Systematic search was conducted using PUBMED, MEDLINE and Google Scholar databases from Afghanistan, India, Pakistan, Nepal, Bangladesh, Sri Lanka, Bhutan, and the Maldives. The electronic search yielded an initial 70 articles and the majority of articles were eliminated. The remaining relevant papers were 18 that became the basis for this review. Review sources were from 2008 to 2019. The majority of South Asian adolescents were not active enough to meet the recommended guidelines for PA. Further, none of the articles were published under self-monitoring PA interventions among age 11 to 19 adolescents in South Asia. Further knowledge concerning Non-Communicable Disease (NCD) and healthy lifestyle factors were poor among school adolescents. The outcomes of this review highlight the need for evidence-based intervention programmes with the potential of self-monitoring to be incorporated into the national education system.